Three-year recordings of tectonic-climate data from Moxa Geodynamic Observatory - Valentin Kasburg; Nina Kukowski (PANGAEA, 2024)
The dataset includes recordings from laser strainmeters, a weather station and several groundwater monitoring wells from Moxa Geodynamic Observatory, located in central Germany. The recordings of the laser strainmeters include measurements along the North-South and East-West directions. The data from the weather station contains recordings of temperature, barometric pressure, wind speed, global radiation, humidity, and snow load. This dataset was compiled for analyzing the causal relationship between climatic variables and strain measurements and covers the period from November 2014 to October 2017. The data has a temporal resolution of one hour, which was calculated from the original temporal resolution of 10 seconds by calculating the mean value. Laser strainmeter measurements underwent error correction and were corrected for Earth tides using the Cleanstrain + package (Langbein, 2010).